SURFACE DECONTAMINATION OF SALMONELLA ENTERICA SEROVAR TYPHIMURIUM ON SHELL EGGS BY VAPORIZED ETHYL PYRUVATE AND PLANT HYDROSOLS - Cakir, Elif; Can, F. Ozge; Durak, M. Zeki (NORTH UNIV CENTER BAIA MARE, 2022)
In this study, the decontamination effects of plants hydrosols, and vaporized ethyl pyruvate were investigated against Salmonella enterica serovar Typhimurium on shell eggs. For hydrosol treatments, the first inoculum level was 6.8 log cfu/g. Inoculated eggs treated with thyme, sage, basil, and their mixed hydrosols and sterilized DI water as a control for 10, 30, 60, and 90 s. Mixed and thyme hydrosols provided the highest log reduction (3 and 3.4 log) in 90 s that can be considered favorable for food decontamination treatments. Inhibition level was determined in the initial population 6.2 log CFU/g of S. typhimurium inactivation at 100 mu L, 500 mu L, and 1000 mu L EP concentrations under ambient and refrigerator conditions for 3, 5, and 7 days. Almost complete inhibition was observed with 1000 mu L of EP at 7 days of storage at 20 degrees C. At refrigerature temperatures, the maximum log reduction was 4.2 after 7 days of storage. In conclusion, this study showed that vaporized EP applications, which are accepted as GRAS, have high antimicrobial activity against S. typhimurium in shell eggs. Hydrosol treatments had lower inhibition levels of S. typhimurium compare to EP treatment. Hydrosol treatments had lower inhibition levels of S. typhimurium compared to EP treatment.
Keywords: Salmonella; egg; Decontamination; Ethyl pyruvate; Thyme hydrosol; Sage hydrosol; COLI O157 H7; STAPHYLOCOCCUS-AUREUS; ENTERITIDIS; INACTIVATION; REDUCTION; BACTERIA; Food Science & Technology